2021
DOI: 10.2147/jpr.s341550
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Perioperative Continuous Intravenous Lidocaine Infusion for 72 Hours on Postoperative Pain and Recovery in Patients Undergoing Hepatectomy: Study Protocol for a Prospective Randomized Controlled Trial

et al.

Abstract: Purpose: Many patients develop severe and persistent pain after hepatectomy delaying postoperative rehabilitation. Studies have suggested that intravenous lidocaine infusion relieved postoperative pain and improved overall postoperative outcomes. However, its efficacy on hepatectomy is still masked, due to the postoperative metabolic change of lidocaine by the liver. We hypothesized that intravenous lidocaine infusion in the perioperative period would lead to postoperative pain reduction and improve the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Lidocaine promotes postoperative recovery by ameliorating analgesic effect. 31 , 32 It was obvious that higher pain scores in our study significantly lowered postoperative recovery quality, especially POH 12 and POH 24; and this was consistent with the study by Licina et al 33 Pain not only causes short-term or long-term fluctuations in hemodynamics, but also delays brain function returning to normal levels, leading to postoperative cognitive dysfunction or abnormal mental activity; afterwards it slows down the postoperative recovery process. 34 , 35 The former was revealed by lower fluctuations of intraoperative hemodynamic parameters (such as MAP and HR) and lower utilization of vasoactive drugs in our study; and the incidence and extent of agitation reduced significantly during extubation, suggesting that lidocaine played a positive role in postoperative brain function recovery.…”
Section: Discussionsupporting
confidence: 89%
“…Lidocaine promotes postoperative recovery by ameliorating analgesic effect. 31 , 32 It was obvious that higher pain scores in our study significantly lowered postoperative recovery quality, especially POH 12 and POH 24; and this was consistent with the study by Licina et al 33 Pain not only causes short-term or long-term fluctuations in hemodynamics, but also delays brain function returning to normal levels, leading to postoperative cognitive dysfunction or abnormal mental activity; afterwards it slows down the postoperative recovery process. 34 , 35 The former was revealed by lower fluctuations of intraoperative hemodynamic parameters (such as MAP and HR) and lower utilization of vasoactive drugs in our study; and the incidence and extent of agitation reduced significantly during extubation, suggesting that lidocaine played a positive role in postoperative brain function recovery.…”
Section: Discussionsupporting
confidence: 89%
“…Lidocaine is one of the most widely used local anesthetics in clinics. Previous studies have shown that patients received a bolus of 1.5–2 mg/kg lidocaine completed within 10 min before the induction of anesthesia followed by continuous infusions of 2 mg/kg/hour lidocaine intravenously during anesthesia could improve QoR-40 scores in patients with abdomen surgery 10 12 , reduce the need for opioids and the intensity of postoperative pain, and extende the time to first request morphine 13 . Lidocaine affects inflammatory cells in vitro, such as by inhibiting priming of human peripheral poly-morphonuclear cells or neutrophils 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study (NCT04295330), we performed a secondary analysis on the prospective clinical trials (NCT05492669) in Medical Center: West China Hospital (Sichuan, China) (14) and screened 130 patients suffering from primary liver cancer who underwent elective hepatectomy from 2019 to 2021. Study eligibility included those undergoing elective hepatectomy for primary liver cancer, aged 18-80 years, American Society of Anesthesiologists (ASA) physical status I-III; with follow-up assessment for NRS.…”
Section: Participantsmentioning
confidence: 99%
“…A model to predict CPSP occurrence by integration of postoperative inflammatory biomarkers and clinical variables had not been developed. This is a secondary analysis on follow-up data from a prospective clinical trial, which aim to explore additional options to alleviate MEP after hepatectomy (14). In this study, we hypothesize that novel inflammatory biomarkers play a key role in CPSP development and when combined with clinical variables can predict the onset of CPSP.…”
Section: Introductionmentioning
confidence: 99%